The Utilization Of Co-Product as Organic Mulch to Improve Nutrient Use Efficiency and Growth of Palm Oil Seedlings in The Main Nursery - Wijayani, Suprih; Kritalisasi, Elizabeth Nanik (Tropical Plantation Journal, 2025)
Replanting is a strategic effort to increase the productivity of oil palm plantations. This effort requires the procurement of quality seedlings, so that maintenance absolutely gets the main attention. This study aims to determine the benefits of co-products to increase nutrient use efficiency (NUE) and the growth of oil palm seedlings in the main nursery. This study used a completely randomized block design with treatments of oil palm co-products (empty bunches, mesocarp fiber, suspended solids applied as mulch on the surface of polybag media, and without co-products) and NPKMg (15:15:6:4) at the rate of 8, 10 and 12 grams/two weekly/seedlings. The treatment  applied at transplanting seedlings from PN to MN until the age of 8 months. The results showed that the growth of oil palm seedlings and NUEwere influenced by the types of co-products and NPKMg rates. Application of oil palm co-products (empty bunches, mesocarp fibers and suspended solids) as surface mulch and NPKMg fertilizer (15:15:6:4)  of 12, 10, and 8 grams/two weekly/seedling can increase the growth of 8-month-old MN oil palm seedlings. The better seedling growth was produced by the application of 8 grams of fertilizer/two weekly/seedling and empty bunches. Application of all co-products can improved NUE in MN nurseries. Improvement of  NUE along with the decrease in the dose of NPKMg application (8 ?10?12 grams/two weekly/seedling).